Quem Será o Herói Dessa Nossa História? Quem Vai Tecer o amanhã?: a disputa de narrativas e representações de Tiradentes e da Inconfidência Mineira Na Ditadura Civil-Militar - Carvalho Neto, Cláudio José de (2019)
born from an effort to try to glimpse the use of the past, or a created-past, as a textual-rhetorical device in the disputes of “narrative”, memory and “writing” of Brazilian national history. In the context of the Military Civil Dictatorship (1964-1985), we sought the records and documents in which it was possible to find the signs and marks of these conflicts between the Regime and its opponents (...)